The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/0886260515585533
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Perceptions and Experiences of Domestic Violence

Abstract: This community-based observational study of 1,325 women seen for antenatal care examined how women in Pakistan define violence against women (VAW), with an emphasis on domestic violence, what an acceptable response to violence is, reasons for remaining silent, and whether participants are willing to disclose incidents of domestic violence to others. Nearly half of the study participants believed that physical violence was VAW. Verbal abuse, controlling behavior by the husband, conflict with in-laws, overburden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 48 publications
5
35
0
1
Order By: Relevance
“…The results of this research demonstrated that the most common reaction among women to the violence was logically speaking to the husband (62.7%) followed by appeasement (35.8%), which were in line with the results of a research by Kargar Jahromi et al (4). Madhani et al reported that women's tolerance was the most frequent reaction and referral to counseling centers and legal complaints as the least frequent cases (37). In the present study, complain to the court was also the least frequent case.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this research demonstrated that the most common reaction among women to the violence was logically speaking to the husband (62.7%) followed by appeasement (35.8%), which were in line with the results of a research by Kargar Jahromi et al (4). Madhani et al reported that women's tolerance was the most frequent reaction and referral to counseling centers and legal complaints as the least frequent cases (37). In the present study, complain to the court was also the least frequent case.…”
Section: Discussionsupporting
confidence: 90%
“…Intimate partner violence (IPV) is a major concern for health, criminal justice, and economies worldwide (Dietrich & Schuett, 2013). Global prevalence is high, with cultural factors influencing both the rates of IPV and attitudes towards the acceptability of using this form of violence (Madhani et al, 2017. For example, evidence suggests that IPV disproportionately affects women from honor cultures in parts of Asia (Mayeda & Vijaykumar, 2016).…”
Section: Pakistanmentioning
confidence: 99%
“…[ 1 ] A recent Pakistani study demonstrated that most women who suffered intimate partner violence did not report the incident and did not seek counseling services. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%